The political economy of rural nutrition transitions: Ultra-processed foods, social eating dynamics, and local health governance in Kawi Mountain Village, East Java - Henny Rosalinda; Rany Purnama Hadi; Adhi Cahya Fahadayna; Primadiana Yunita (Priviet Social Sciences Journal, 2026)
The increasing consumption of Ultra-Processed Foods (UPFs) has become a major public health concern, particularly in Low- and Middle-Income Countries (LMICs) undergoing rapid nutritional transitions. While previous studies have primarily focused on urban populations, limited research has examined how structural determinants influence Ultra-Processed Food (UPF) consumption among adolescents in rural communities experiencing economic transformation. This study explores the determinants of adolescent UPF consumption in Gunung Kawi Village, East Java, Indonesia, using H.L. Blum's Determinants of Health Framework integrated with the Commercial Determinants of Health (CDoH). A qualitative descriptive design was employed, involving in-depth interviews with adolescents, parents, healthcare workers, and food vendors, complemented by field observations. Data were analyzed thematically according to Blum's four determinants: environmental, lifestyle, health service, and biological determinants. The findings reveal that the local food environment has been transformed by tourism development and commercial expansion, increasing adolescents' exposure to UPFs. Lifestyle behaviors were shaped by convenience and affordability, and household dietary practices normalized UPF consumption within families. Health services continue to prioritize maternal and child health and provide limited nutrition education targeting adolescent dietary behaviors. The study also identified an affordability trap, whereby economic and time constraints encourage households to rely on inexpensive, processed foods. By integrating Blum's Determinants of Health with the Commercial Determinants of Health, this study demonstrates that adolescent UPF consumption is driven by interacting structural and behavioral determinants rather than individual food choices alone. These findings highlight the need for multisectoral interventions that improve rural food environments, strengthen nutrition education, and support healthier household food practices during Indonesia's ongoing nutrition transition.